Analisis Pengelolaan Akuntansi Keuangan pada Fungsi Laporan Keuangan CV. Rensa Wallpaper - Adi Prihanisetyo; Ugroseno Damara Prasadhana Handoyo; Susanti Susanti (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This research is motivated by the importance of financial management, especially financial accounting, as the key to company sustainability, however, it was found that CV. Rensa Wallpaper, although it has made financial reports (Balance Sheet and Profit and Loss Statement), its implementation is not in accordance with SAK ETAP and there is no urgency to make other reports (such as equity change reports and cash flow reports). The type of research used is a case study research using a qualitative method, namely a method that collects, compiles, interprets, and analyzes data to solve the problems faced. While the research approach used is a descriptive approach. The data used in this study are primary data and secondary data. Overall, the results of the study indicate that although CV. Rensa Wallpaper carries out financial management that includes four basic elements (Planning, Organizing, Directing, and Controlling), the implementation of its financial reporting is still incomplete and not fully in accordance with SAK ETAP due to the incompleteness of the reports presented (there is no Statement of Changes in Equity and Cash Flow Statement) and the existence of account items that are not presented in the Balance Sheet.